Electronic Health Records Design in the Nutrition Care Center of Teaching Factory at Politeknik Negeri Jember, Indonesia - Deharja, Atma; Yunus, Muhammad; Santi, Maya Weka (International Journal of Health and Information System, 2023)
The Nutrition Care Center (NCC) is one of the teaching factories (TEFA) at Politeknik Negeri Jember that provides community nutrition services. Preliminary data collection found that the factory did not have complete health database of their staff so that nutritionists find it difficult to screen for non-communicable disease risk factors. In this study, the use of Electronic Health Record (EHR) equipped with Clinical Decision Support System (CDSS) was incorporated to record, retrieve, archive, and update patients and other medical records in the NCC. This system provides easier health record management for the nutritionist team at the NCC TEFA Politeknik Negeri Jember. Medical records help them conduct screening on non-communicable disease (NCD) risk factors and make clinical decision support for doctors/counselors which have missions to reduce NCD cases in the productive age. This study used a waterfall method model and collected data through a literature review, observation, and interviews. The results produced an application of a clinic database management in which all data and information could be integrated well to improve the quality of services and facilitate data storage and access. This study concludes that the EHRs generates quick and accurate information to support operations and decision-making in the NCC.